Polydactyly and syndactyly linked to GLI3 and TBX5 mutations: A pediatric case report - R. Leonardi; G. Pellino; E. Floridia; M. Lo Bianco; M. Ruggieri; SY. Cho; V. Pavone; P. Pavone; A. Polizzi (Global Medical Genetics)
Background: Polydactyly and syndactyly, which are commonly encountered congenital limb deformities, rarely occur together and are linked with significant genetic mutations. This report sheds light on a unique co-presentation involving mutations in both the GLI3 and TBX5 genes, offering a deeper understanding of the genetic interactions that may influence limb development. This case report is important to increase our knowledge on genetic bases of limb malformations. Case presentation: We report the case of an 8-month-old boy, born to non-consanguineous parents, presenting with both polydactyly and syndactyly in his limbs, in particular, complete syndactyly between the third to fifth fingers and post-axial polydactyly of the feet. His father showed a similar phenotype. Genetic testing identified a pathogenic heterozygous variant in the GLI3 gene (c .3762 T > A, p.(Tyr1254 *)) and a variant of uncertain significance in the TBX5 gene (c .1063 C>T, p.(Arg355Cys)). Conclusions: This case highlights the complex nature of diagnosing and managing congenital limb deformities driven by genetic factors. It underscores the critical importance of comprehensive genetic testing in determining the etiology of limb malformations. The GLI3 variant, classified according to ACMG guidelines as a class IV mutation, likely results in a truncated protein due to a premature stop codon, confirmed by family segregation analysis indicating its paternal origin, suggesting autosomal dominant inheritance. Notably, the TBX5 gene variant, often associated with Holt-Oram syndrome—which is characterized by only hand skeletal anomalies and early-onset atrial fibrillation—suggests a risk of developing cardiac issues that are not currently present but may emerge as the child grows. This potential for evolving clinical manifestations necessitates vigilant long-term monitoring and may influence future medical management and therapeutic approaches.